Optimization of Wind-Marine Hybrid Power System Configuration Based on Genetic Algorithm - Shi, Hongda; Li, Linna; Zhao, Chenyu (Journal of Ocean University of China, 2017)
Multi-energy power systems can use energy generated from various sources to improve power generation reliability. This paper presents a cost-power generation model of a wind-tide-wave energy hybrid power system for use on a remote island, where the configuration is optimized using a genetic algorithm. A mixed integer programming model is used and a novel object function, including cost and power generation, is proposed to solve the boundary problem caused by existence of two goals. Using this model, the final optimized result is found to have a good fit with local resources.